2009
DOI: 10.1161/circresaha.108.191114
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Prostacyclin by Steady Laminar Shear Stress Suppresses Tumor Necrosis Factor-α Biosynthesis via Heme Oxygenase-1 in Human Endothelial Cells

Abstract: Abstract-Cyclooxygenase (COX)-2 is among the endothelial genes upregulated by uniform laminar shear stress (LSS), characteristically associated with atherosclerotic lesion-protected areas. We have addressed whether the induction of COX-2-dependent prostanoids in endothelial cells by LSS plays a role in restraining endothelial tumor necrosis factor (TNF)-␣ generation, a proatherogenic cytokine, through the induction of heme oxygenase-1 (HO)-1, an antioxidant enzyme. In human umbilical vein endothelial cells (HU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 64 publications
3
95
0
1
Order By: Relevance
“…It has been recently reported that vascular PGI 2 may be involved in the regulation of eNOS expression (122). Importantly, Di Francesco et al showed that cyclooxygenase-2-dependent PGI 2 induced by steady laminar shear stress upregulates heme-oxygenase 1, which halts the effects of TNFa in human ECs (31). Given that fluvastatin has been shown to increase expression of PGI 2 synthase and PGI 2 in human ECs (100), this pathway may also participate in the vasoprotective effects of statins.…”
Section: Effects Of Statins On Other Enzymatic Systems and Pathways Imentioning
confidence: 98%
“…It has been recently reported that vascular PGI 2 may be involved in the regulation of eNOS expression (122). Importantly, Di Francesco et al showed that cyclooxygenase-2-dependent PGI 2 induced by steady laminar shear stress upregulates heme-oxygenase 1, which halts the effects of TNFa in human ECs (31). Given that fluvastatin has been shown to increase expression of PGI 2 synthase and PGI 2 in human ECs (100), this pathway may also participate in the vasoprotective effects of statins.…”
Section: Effects Of Statins On Other Enzymatic Systems and Pathways Imentioning
confidence: 98%
“…The exception is performed by the fluorinated series of compounds, whose ethyl ester derivatives seem to be more selective than the bulkier analogues (i-propyl and n-butyl derivatives). Since the hydrolysis of the ester can occur at least to some extent in vivo, ester compounds 26-32 and 59-66 were evaluated in comparison with the corresponding acid (19)(20)(21)(22)(23)(24)(25) [25g]. In general the ester derivatives proved to be more effective and selective toward COX-2 with respect to acid derivatives and only in the case of 3-F phenyl substituted derivatives the acid compound 23 and the esters compounds 30, 61 and 62 displayed closer potencies.…”
Section: Biological and Pharmacological Evaluationmentioning
confidence: 99%
“…COX-2 is among the endothelial genes upregulated by uniform laminar shear stress (LSS), characteristically associated with atherosclerotic lesion-protected areas [10c]. We have recently enlightened a central role played by LSS-induced COX-2-dependent prostacyclin in restraining endothelial inflammation [20]. Thus, inhibition of COX-2-dependent prostacyclin might contribute to acceleration of atherogenesis in patients taking tNSAIDs and NSAIDs selective for COX-2 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Two clones were sequenced in comparison with a sequence from EMBL Databank (accession number AF027740) and a conservative mutation in [19] and for PGE 2 production by a validated radioimmunoassay [17]. Clone D8L was selected for its mPGES-1 high expression level.…”
Section: Cloning and Expression Of Human Mpges-1 In A549 Cellsmentioning
confidence: 99%
“…This compound was dissolved in DMSO and 2 l of vehicle or stock solution was added to 1ml of cell suspension. PGE 2 , 10 TXB 2 (the stable hydrolysis product of TXA 2 ), PGF 2 and 6-keto-PGF 1 (the hydrolysis product of PGI 2 ) levels were measured in cell culture media by previously described and validated radioimmunoassay techniques [17,19,23], while COX-2, COX-1, mPGES-1, mPGES-2, cPGES, TXS and PGIS protein levels were evaluated in cell lysates by previously described Western blot techniques [17,19].…”
Section: Isolation Of Human Monocytes and Pharmacological Treatmentmentioning
confidence: 99%